Universal Values: Spread in China and the Essence - Zhang, Yonghong (American Journal of Humanities and Social Sciences, 2013)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:8.0pt; mso-para-margin-left:0in; line-height:107%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] --> To explore the "universal values" ideology with the Western "democracy, freedom, equality, human rights and so forth “as the core can enhance our understanding of it. The so-called "Universal values" are the core values of the West. Its spread in China has a profound background both internationally and domestically. This ideology has had a negative influence on people, resulting in a transmutation of their world outlook. Only by using the Marxist class viewpoint and class analysis approach, could we boycott its negative effects. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]>